Microfluidics : fundamental, devices and applications - Song, Yujun; Cheng, Daojian; Zhao, Liang (Weinheim, Germany : Wiley-VCH, 2018)
The first book offering a global overview of fundamental microfluidics and the wide range of possible applications, for example, in chemistry, biology, and biomedical science. As such, it summarizes recent progress in microfluidics, including its origin and development, the theoretical fundamentals, and fabrication techniques for microfluidic devices. The book also comprehensively covers the fluid mechanics, physics and chemistry as well as applications in such different fields as detection and synthesis of inorganic and organic materials. A useful reference for non-specialists and a basic guideline for research scientists and technicians already active in this field or intending to work in microfluidics.
Introduction: The Origin, Current Status, and Future of Microfluidics / Kin Fong Lei -- Fundamental Concepts and Physics in Microfluidics / Yujun Song, Xiaoxiong Zhao, Qingkun Tian, Hongxia Liang -- Microfluidics Devices: Fabrication and Surface Modification / Zhenfeng Wang, Tao Zhang -- Numerical Simulation in Microfluidics and the Introduction of the Related Software / Zheng Zhao, Adrian Fisher, Daojian Cheng -- Digital Microfluidic Systems: Fundamentals, Configurations, Techniques, and Applications / Mohamed Yafia, Bara J Emran, Homayoun Najjaran -- Microfluidics for Chemical Analysis / Peng Song, Adrian C Fisher, Luwen Meng, Hoang V Nguyen -- Microfluidic Devices for the Isolation of Circulating Tumor Cells (CTCs) / Caroline C Ahrens, Ziye Dong, Wei Li -- Microfluidics for Disease Diagnosis / Jun-Tao Cao -- Gene Expression Analysis on Microfluidic Device / Liang Zhao -- Computational Microfluidics Applied to Drug Delivery in Pulmonary and Arterial Systems / Clement Kleinstreuer, Zelin Xu -- Microfluidic Synthesis of Organics / Hongxia Liang, Yujun Song -- Microfluidic Approaches for Designing Multifunctional Polymeric Microparticles from Simple Emulsions to Complex Particles / Jongmin Kim, Chang-Soo Lee -- Synthesis of Magnetic Nanomaterials / Ali Abou-Hassan -- Microfluidic Synthesis of Metallic Nanomaterials / Jugang Ma, Yujun Song -- Microfluidic Synthesis of Composites / Junmei Wang, Yujun Song -- Microfluidic Synthesis of MOFs and MOF-Based Membranes / Fernando Cacho-Bailo, Carlos Téllez, Joaquin Coronas -- Perspective for Microfluidics / Yujun Song, Daojian Cheng.
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed January 10, 2018).
Keywords: Microfluidics; TECHNOLOGY & ENGINEERING -- Hydraulics; Microfluidics; Electronic books